Effects of Probiotic Intervention on Markers of Inflammation and Health Outcomes in Women of Reproductive Age and Their Children - Kwok, Kah Onn; Fries, Lisa R.; Silva-Zolezzi, Irma; Thakkar, Sagar K.; Iroz, Alison; Blanchard, Carine (Frontiers in Nutrition, 2022)
The human intestinal microbiota has been shown to be modulated during inflammatory conditions. Probiotic administration has been shown to affect the immune system and cytokines expression which can affect inflammation and health outcomes. There seems to be an association between the mother’s intestinal microbiota and inflammation biomarkers, which both may contribute to newborn early life immune and metabolic programming and impact short and long-term health outcomes. Probiotic supplementation during pregnancy has been shown to influence metabolic health, immunity, and gastrointestinal health of the mother, and can also have carry-over benefits to infants such as infant allergy risk reduction. Therefore, this review focuses on the evidence of probiotic administration in women of reproductive age, including during pregnancy and its impact on inflammatory markers and on maternal and infant health. We performed a PubMed search for articles published in English in the last 20 years. Immune markers were narrowed to serum and breast milk levels of TNF-α, IL-6 and TGF-β, IgA and IL-10. Studies that investigated the beneficial effects of interventions in women with gestational diabetes mellitus, polycystic ovarian syndrome, and infant allergy management are summarized. These results show a beneficial or neutral effect on selected health outcomes and that it is safe for woman and their infants. The effect of probiotics on modulation of inflammatory markers was probiotic specific. More research is needed to further our understanding of the mechanisms underlying the effects of probiotics on inflammation and how these effects improve health outcomes.